Evidence for exotic Hadron contributions to [lambda]0b→J/[psi]pπ- decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2016)
A full amplitude analysis of Λ0b→J/ψpπ− decays is performed with a data sample acquired with the LHCb detector from 7 and 8 TeV pp collisions, corresponding to an integrated luminosity of 3 fb−1. A significantly better description of the data is achieved when, in addition to the previously observed nucleon excitations N→pπ−, either the Pc(4380)+ and Pc(4450)+→J/ψp states, previously observed in Λ0b→J/ψpK− decays, or the Zc(4200)−→J/ψπ− state, previously reported in B0→J/ψK+π− decays, or all three, are included in the amplitude models. The data support a model containing all three exotic states, with a significance of more than three standard deviations. Within uncertainties, the data are consistent with the Pc(4380)+ and Pc(4450)+ production rates expected from their previous observation taking account of Cabibbo suppression.
*LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 719 weitere Personen]
Im Titel sind die Zahl 0 und das Zeichen - hochgestellt
Im Titel ist der Buchstabe b tiefgestellt
Im Titel sind "lambda" und "psi" als griechische Buchstaben dargestellt
Gesehen am 14.07.2020